Pendugaan Kemunduran Benih dengan Uji Fisiologi dan Biokimiawi - Gani Jawak; Eny Widajati; Devi Liana; Tri Astuti (Fakultas Pertanian, Universitas Timor, 2022)
The seed viability test is one of the routine tests carried out in the seed certification process. Decreasing the viability of seeds can be done biochemically and physiologically. This research aimed to study of seeds deterioration through physiological and biochemical tests. This study used two lots of long bean seeds (high and low lot). Physiologically, the seed viability test was carried out by means of germination test and biochemical by means of respiration test using tetrazolium (TTZ) staining technique and titration method. The experiment designed by completely randomized design one factor. Data were analyzed by anova test and Pearson correlation. The results of research showed that the seed lot treatment was significantly on the tetrazolium test and the total dry weight of sprouts, while the vigor index, seed germination, and respiration index measurements did not show significant. There was a high positive correlation in the high respiration rate of high seed lots and low seed lot seeds on total dry weight of germination, germination, vigor index, and tetrazolium test. Therefore, biochemical tests with TTZ and respiration with titration methods can be used as alternatives to predict rapid deterioration of seeds.